SYSTEM OF ADAPTIVE CONTROL IN ELECTROCONTACT WELDING OF SELF-FLUXING ALLOYS POWDERS - O. O. Kuznechik; K. E. Beljavin (Литьë и металлургия)
The technical characteristics, functional and structural schemas of the system of powder electrocontact welding adaptive control are given.